2009
DOI: 10.1126/science.1168676
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Antigen-Specific and Infected Cells in Situ Predicts Outcomes in Early Viral Infection

Abstract: In the early stages of viral infection, outcomes depend on a race between expansion of infection and the immune response generated to contain it. We combined in situ tetramer staining with in situ hybridization to visualize, map, and quantify relationships between immune effector cells and their targets in tissues. In simian immunodeficiency virus infections in macaques and lymphocytic choriomeningitis virus infections in mice, the magnitude and timing of the establishment of an excess of effector cells versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
168
2
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(182 citation statements)
references
References 20 publications
11
168
2
1
Order By: Relevance
“…During MHV68 infection, plasmacytoid dendritic cells are recruited to the lung and upregulate major histocompatibility complex (MHC) class II (40 (45). High levels of antigen exposure are key mediators of CD8 ϩ T cell exhaustion (46)(47)(48). In support of this mechanism, early mitigation of MHV68 replication in IFNAR1 Ϫ/Ϫ mice resulted in marked improvement in CD8 ϩ T cell TNF-␣ and IFN-␥ production, as well as reduced PD-1 expression.…”
Section: Ifnar1mentioning
confidence: 80%
“…During MHV68 infection, plasmacytoid dendritic cells are recruited to the lung and upregulate major histocompatibility complex (MHC) class II (40 (45). High levels of antigen exposure are key mediators of CD8 ϩ T cell exhaustion (46)(47)(48). In support of this mechanism, early mitigation of MHV68 replication in IFNAR1 Ϫ/Ϫ mice resulted in marked improvement in CD8 ϩ T cell TNF-␣ and IFN-␥ production, as well as reduced PD-1 expression.…”
Section: Ifnar1mentioning
confidence: 80%
“…Recently, a combined in situ tetramer staining and in situ hybridization approach showed that relative rates of increase in Agspecific effector CD8 + T cells and virally infected targets during the early stage predict the outcome of viral infection (56). For example, LCMV clone 13 preferentially infects fibroblastic reticular cells, which enables this clone to spread and replicate tremendously faster than LCMV-Armstrong, thereby exceeding the capacity of initial immune response to reduce the basic rate of replication.…”
Section: Discussionmentioning
confidence: 99%
“…These types of infections often lead to high levels of virus-derived peptide antigens presented by MHC class I molecules on a variety of infected cell types, depending on the tropism of the virus. Exhaustion of antiviral CD8 1 T cells occurs rapidly and extensively in chronic LCMV infection, which is likely attributable to the fact that LCMV infects in vivo a large variety of hematopoietic as well as non-hematopoietic cells and therefore leads to high antigen burden perceived by LCMVspecific CD8 1 T cells [70,78]. Exhaustion of HIV-specific CD8…”
Section: Antigen Loadmentioning
confidence: 99%